(3OjhGf Ydj GdZQGH GdUaGbSjs
(3ChdgG (B:s
(3GdMeO ddg, bGd Gdabjg GdCOjH GdHGQY Ydj GdZQGH GdUaGbSj fLe GdSYGOI aj YdGc JUYOG hGdfUQ aj eGVj MSGec NdOG s
(3BNQgG (B:s
(3jgfjc ejdGO GdZdGe GdPj eJYc Gddg HejdGO efYc Gddg Hg OGFeG MJi JQi ChdGO ChdGOg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B162 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTGPdj GdfjaQ HJhfS (B(108) s
Keywords: (3GdCOHs